Intentions to consume dietary supplements among Gen Y: extended planned behaviour model - Chutima Chaichana; Sebastian Kot; Bilal Khalid; Singha Chaveesuk (Verslas teorija ir praktika, 2025)
The attention drawn by COVID-19 in terms of health improvement has included usage of dietary supplements; it is viewed as a means of boosting immune systems and hence supporting a better overall physical condition, The research intends to establish the determining aspects of the intention to consume dietary supplements among those of Gen Y. Extended theory of planned behavior was adopted to develop the framework for this study. The empirical study used primary data generated from Gen Y individuals aware of their consumption. A total of 449 respondents were collected and data were analyzed using structural equation modeling (SEM). The results indicated five positive and significant influences on the consumption of dietary supplements by Gen Y: the perceived behavioral control over the use of supplements; need for supplement consumption; health information-seeking behavior; perceived social pressure; and trust in the supplement brand. It is evident that attitude toward dietary supplements significantly mediates the relationship between the social media subjective norm and health information seeking and the intention to consume the dietary supplements. Despite increasing studies on dietary supplement consumption, not much has been done on the aspects influencing intention to consume dietary supplements on the part of Gen Y.
Keywords: Consumer Attitudes and Food Labeling; Behavioral Health and Interventions; Nutrition, Genetics, and Disease